Residual Effect of Chromium on Early Growth of Fluted Pumpkin (Telfairia occidentalis Hook F) in an Ultisol - ER Orhue; FO Uzu (Journal of Applied Sciences and Environmental Management)
These greenhouse and field trials were aimed at determining the residual influence of Cr on some agronomic characters, nutrient content, nutrient uptake and crude protein content of fluted pumpkin in soils previously treated with 0, 50, 100, 200 mg Cr(NO3). .9H2O per 5 kg soil in the greenhouse and 0, 20, 40, 80 kgha-1 Cr ((NO3). 9H2O in the field trial. The completely and randomized complete block designs were used in the greenhouse and field trials respectively. The soils used were left uncultivated for 10 weeks prior to the residual trials. Results revealed that the plant height, stem girth, leaf area, number of leaves, dry matter yield, crude protein nutrient content and uptake declined with increased Cr concentrations. As the soil Cr concentration increased, the Cr content and uptake by root and shoot increased. There were however depressions in Cr uptake by the root at 100 mgCr in the greenhouse and in Cr uptake by the root and shoot at 40 kgha-1 concentration in the field trial. However, the root accumulated higher Cr than the shoot whereas the shoot had higher nutrient content, nutrient uptake, crude protein, and dry matter yield. The soil nutrient components were not affected negatively by the increased Cr concentrations. The Cr content of the soil was however, not exhausted at the end of these trials. @JASEM